High-stretchability pillararene polypropylene hydrogel and preparation method thereof
By introducing columnar aromatic supramolecular polymer network into acrylic hydrogels, the problems of poor impact and puncture resistance of traditional hydrogels are solved, and high tensile properties and excellent mechanical properties are achieved, which are suitable for a variety of applications. field.
Patent Information
- Application Number
- CN202411626254.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The traditional acrylic hydrogel has a low elongation of break after curing, and its impact and puncture resistance are relatively poor, which limits its development in many application fields.
The columnar aromatic compound, 4,4-bipyridine and polyethylene glycol are mixed to form a supramolecular polymer and added to the aqueous solution of acrylamide, sodium acrylate and N,N-methylenebisacrylamide, through Metal ions and initiators are added to produce a highly stretchable columnar aromatic polypropylene hydrogel.
It significantly improves the mechanical and energy dissipation of the hydrogel, increases maximum elongation and ductility, while not sacrificing mechanical strength, and improves impact and puncture resistance.
Smart Images

Figure CN119285865A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of supramolecular materials and relates to a high-stretchability pillar aromatic polypropylene hydrogel and a preparation method thereof. Background Art
[0002] Hydrogels based on acrylic (acrylamide, acrylic acid, etc.) are widely used in biomedicine, water treatment and other fields. They usually have excellent water absorption and stability, and have been studied by many researchers so far. Xiong Lijun and others from Wuhan University of Technology used acrylamide and acrylic acid as monomers, added lithium algae to construct a network through electrostatic action, and generated an interpenetrating double network hydrogel with a maximum tensile stress of about 137KPa. Li Zhaoxia and others from the University of Chinese Academy of Sciences added N-isopropyl acrylamide to acrylamide, and used polyvinyl alcohol diacrylate and polycaprolactone diacrylate as crosslinkers to construct a network to generate an interpenetrating double network hydrogel. In addition to having good mechanical properties, the hydrogel has excellent temperature sensitivity. Wang Xiaohui and others from South China University of Technology added lithium chloride (LiCl) and cellulose nanofibers to polyacrylamide hydrogel to prepare a hydrogel with a tensile strength of 0.09-0.25MPa, which has good freezing resistance and water retention. However, the currently prepared acrylic hydrogel has a low elongation at break after curing, and its impact and puncture resistance are relatively poor, which has limitations in many application fields.
[0003] Therefore, synthesizing acrylic hydrogels with good mechanical properties is the primary task to promote the further development of this type of materials. Summary of the invention
[0004] Aiming at the problem that the conventional propylene-based hydrogel has low elongation at break after curing and relatively poor impact resistance and puncture resistance, the present invention proposes a novel high-stretchability pillar aromatic polypropylene hydrogel and a preparation method thereof.
[0005] In order to achieve the above object, the present invention is implemented by adopting the following technical solutions: A method for preparing a high-stretchability pillar aromatic polypropylene hydrogel comprises the following steps: a pillar aromatic compound, a 4,4-bipyridine compound and polyethylene glycol are mixed to obtain a supramolecular polymer, the supramolecular polymer is then added to an aqueous solution of acrylamide, sodium acrylate and N,N-methylenebisacrylamide, and metal ions, initiators and promoters are added to obtain the hydrogel.
[0006] The method for preparing the pillar aromatic supramolecular polymer network provided by the present invention is simple, has mild reaction conditions and is easy to implement; adding the polymer to the propylene hydrogel can greatly improve its mechanical properties, bring more excellent mechanical properties and energy dissipation to the material, and has great potential in the preparation of toughening agents.
[0007] The preparation method of the above-mentioned high-stretchability pillar aromatic polypropylene hydrogel comprises the following specific steps: (1) Add pillar aromatic compound a and 4,4-bipyridine compound b into water and mix them at room temperature for 1.5-3 hours to obtain a pseudorotaxane, wherein the structural formula of pillar aromatic compound a is: , The structural formula of 4,4-bipyridine compound b is: .
[0008] (2) Adding diepoxy polyethylene glycol and four-arm epoxy polyethylene glycol to the pseudorotaxane obtained in step (1) to obtain a mixed solution H, adding lithium hydroxide to carry out a catalytic reaction after the mixture is completely dissolved, thereby obtaining a sodium acetate-modified pillar[5]arene supramolecular polymer.
[0009] (3) acrylamide, sodium acrylate and N,N-methylenebisacrylamide are dissolved in water, and the supramolecular polymer obtained in step (2) is added. Under the protection of an inert gas, a metal ion solution is added, and the mixture is mixed evenly to obtain a mixed solution P. Then, an initiator and a promoter are added, and the mixture is allowed to react to obtain a highly stretchable supramolecular hydrogel.
[0010] Preferably, in step (1), the molar ratio of the pillar aromatic compound a to the 4,4-bipyridine compound b is 1:1.
[0011] Preferably, the mass fraction of pseudorotaxane in the mixed solution H of step (2) is 9-11%, the molecular weights of diepoxy polyethylene glycol and four-arm epoxy polyethylene glycol are 1000-20000; and the molar ratio of diepoxy polyethylene glycol to four-arm epoxy polyethylene glycol is (35-40):1.
[0012] Preferably, in step (3), the mass ratio of supramolecular polymer: acrylamide: sodium acrylate: N,N-methylenebisacrylamide is (0.2-2): (95-105): (95-105): (0.8-1.2). If the supramolecular polymer network is excessive, the hydrogel dynamics will become stronger and the tensile properties will decrease. The inert gas is nitrogen, and the metal ion solution is any one of copper nitrate solution, zinc nitrate solution, ferrous nitrate solution, cobalt nitrate solution, and nickel nitrate solution, and copper nitrate solution is most preferred. The concentration of metal ions in the mixed solution P is 0.05-0.2 g / mL. Excessive addition of metal ions will make it difficult for the hydrogel to gel.
[0013] Preferably, in step (3), the initiator is ammonium persulfate or potassium persulfate, and the accelerator is tetramethylethylenediamine.
[0014] The present invention also provides a high-stretchability pillar aromatic polypropylene hydrogel prepared by the method.
[0015] The present invention uses a supramolecular polymer network of columnar [5] aromatic hydrocarbons modified with sodium acetate as a toughening agent and combines it with propylene hydrogels through metal ions. Compared with traditional propylene hydrogels, the mechanical properties and energy dissipation are significantly improved. The addition of the supramolecular polymer network of columnar aromatic hydrocarbons can significantly improve the toughness and tensile properties of the original hydrogel, and promote the maximum elongation and ductility without sacrificing the mechanical strength of the polymer.
[0016] Compared with the prior art, the advantages and positive effects of the present invention are: (1) The present invention provides a pillar aromatic supramolecular polymer network with excellent performance, easy synthesis and mild synthesis conditions. The host-guest interaction of pillar [5] aromatics and 4,4-bipyridine makes the supramolecular polymer network have good dynamic properties. It is added as a toughening agent to polypropylene-based hydrogel, so that the hydrogel has better mechanical properties and energy dissipation, and its maximum elongation and ductility are greatly enhanced without sacrificing mechanical strength.
[0017] (2) The pillar aromatic hydrocarbon supramolecular polymer network provided by the present invention has a tensile strength of 0.14 MPa and a maximum elongation of 1600% when it is in a suitable ratio with acrylamide and sodium acrylate. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a real picture of the stretched hydrogel prepared in Example 1.
[0019] Figure 2 The tensile stress-strain diagram of the hydrogel prepared after adding different metal ions.
[0020] Figure 3 The tensile stress-strain diagram of the hydrogel prepared with different metal ion addition amounts.
[0021] Figure 4 Cyclic tensile stress-strain diagram of the hydrogel.
[0022] Figure 5 Cyclic compression stress-strain diagram of hydrogel. DETAILED DESCRIPTION
[0023] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0025] Example 1 The pillar aromatic compound a in this embodiment is a pillar [5] aromatic modified with sodium acetate, and its synthesis route is as follows: .
[0026] 0.5 g of methoxy column [5] aromatic hydrocarbon (CAS No.: 1188423-16-6) was added to 50 mL of chloroform. 3.34 g of boron tribromide solution (mass fraction: 99.9%) was slowly added under nitrogen protection. The reaction was stirred at room temperature for 72 h at a stirring rate of 200 rpm. After the reaction was completed, 50 mL of deionized water was added to precipitate. The upper liquid was discarded and the precipitate was washed once with 0.5 mol / L hydrochloric acid solution and chloroform to obtain 0.35 g of white solid hydroxy column [5] aromatic hydrocarbon (CAS No.: 1187983-02-3) with a yield of 86%. The above operation was repeated to obtain a sufficient amount of hydroxy column [5] aromatic hydrocarbon for use.
[0027] 0.5 g of hydroxyl column [5] aromatic hydrocarbons was weighed and dissolved in 30 mL of acetonitrile. 3 g of potassium carbonate was added and stirred for 1 h under a nitrogen atmosphere at a stirring rate of 200 rpm. Then 0.034 g of sodium iodide and 2.79 g of ethyl bromoacetate were added and heated to reflux at 90 ° C for 24 h under a nitrogen atmosphere. After the reaction was completed, the filtrate was filtered and collected, and the crude product was dried to obtain a crude product. The crude product was separated by column chromatography (eluent: dichloromethane / ethyl acetate = 20:1, v / v) to obtain 0.72 g of ethyl acetate oxy-modified column [5] aromatic hydrocarbons (CAS No. 1235482-11-7) with a yield of 56.5%.
[0028] Weigh 0.3 g of ethyl acetate-modified column [5] aromatic hydrocarbons, add them to 40 mL of tetrahydrofuran, add 20 mL of ethanol, add 20 mL of 40% sodium hydroxide solution, and heat and reflux at 70°C for 10 h. After the reaction is completed, add 20 mL of 0.5 mol / L hydrochloric acid and stir thoroughly, acidify for 10 min, collect the precipitate by filtration, wash the precipitate twice with deionized water, and dry to obtain 0.18 g of ethyl acetate-modified column [5] aromatic hydrocarbons (CAS No. 1235482-12-8), with a yield of 74%.
[0029] Weigh 0.15 g of acetoxy-modified column [5] aromatics, add to 50 mL of deionized water, add 0.04 g of sodium hydroxide, stir at room temperature at 200 rpm for 12 h, decompress and spin dry the water, and obtain 0.15 g of sodium acetate-modified column aromatics with a yield of 89%. Characterize the structure of the synthesized sodium acetate-modified column [5] aromatics: weigh an appropriate amount of the final product into a nuclear magnetic resonance tube, dissolve it in deuterated water, and test it using a nuclear magnetic resonance spectrometer at 25°C. After testing, the spectrum has no impurity peaks, proving that the product has reached a high purity. The nuclear magnetic resonance data are as follows: 1 H NMR (400MHz, D2O, 298K) δppm 6.77 (s, 10H), 4.50 (d, J =16.0Hz,10H),4.26(d, J = 16.1 Hz, 10H), 3.83 (s, 10H).
[0030] The 4,4-bipyridine derivative in this example is synthesized by the following route: .
[0031] 1.95 g of 1,6-dibromohexane and 0.91 g of potassium thioacetate were added to 50 mL of dry tetrahydrofuran, and the mixture was heated under reflux at 60° C. for 12 h. After the reaction was complete, the mixture was filtered and the solution was spin-dried to obtain a crude product. The crude product was separated by column chromatography (eluent: petroleum ether / ethyl acetate = 9:1, v / v) to obtain 0.9 g of pure thioacetoxybromohexane (CAS No. 479072-66-7) with a yield of 49%. This step was repeated to obtain a sufficient amount of thioacetoxybromohexane for use.
[0032] Weigh 1 g of thioacetoxybromohexane and 0.26 g of 4,4-bipyridine (CAS: 553-26-4), mix them in 100 mL of acetonitrile, and react at 80°C for 96 h. After the reaction is completed, spin dry, dissolve in 5 mL of methanol, and then add 15 mL of ether. Solid precipitates and the obtained solid is filtered to obtain 0.79 g of thioacetoxy 4,4-bipyridine (CAS No. 871028-80-7) with a yield of 74%.
[0033] 0.5 g of thioacetoxy 4,4-bipyridine was dissolved in 50 mL of methanol. Under nitrogen protection, 1.2 g of acetyl chloride was added dropwise at -78 °C (addition time was 10-15 s). After the addition was completed, the temperature was kept at -78 °C for 10 min, and then the reaction was continued at room temperature for 3 h. After the reaction was completed, the solvent was dried to obtain 0.4 g of yellow solid mercaptohexane-modified 4,4-bipyridine with a yield of 92%.
[0034] The structure of the synthesized mercaptohexane-modified 4,4-bipyridine was characterized. An appropriate amount of the final product was weighed into a nuclear magnetic resonance tube, dissolved in deuterated methanol, and tested using a nuclear magnetic resonance spectrometer at 25°C. The obtained spectrum had no impurity peaks, proving that the product reached a high purity. The nuclear magnetic resonance data are as follows: 1 H NMR (400 MHz, CD3OD, 298K)δ ppm 9.34 – 9.27 (m,4H), 8.70 (d, J = 6.3 Hz, 4H), 4.77 (t, J = 7.6 Hz, 4H), 3.35 (s, 4H), 2.52 (tt, J = 7.1, 4H), 2.12 (p, J = 7.6 Hz, 4H), 1.72 – 1.59 (m, 4H), 1.59 – 1.40 (m, 4H).
[0035] Weigh 0.15 g of acetoxy-modified column [5] aromatics and 0.056 g of mercaptohexane-modified 4,4-bipyridine and add them to 60 mL of deionized water. Mix at room temperature for 2 h to obtain pseudorotaxane. Place an appropriate amount of pseudorotaxane product in a nuclear magnetic resonance tube, dissolve it in deuterated water, and test it using a nuclear magnetic resonance spectrometer at 25 ° C. The obtained nuclear magnetic resonance data are: 1 H NMR (400 MHz, D2O, 298 K) δppm8.58 (s, 4H), 8.38 (s, 4H), 7.09 (s, 10H), 4.34 (s, 20H), 3.91 (s, 10H), 3.35(s, 4H), 2.07 (s, 4H), 1.05 (s, 4H),0.79 (s, 8H), 0.62 (s, 4H). The spectrum contains no impurity peaks, which proves that the product has reached a high purity.
[0036] To the obtained pseudorotaxane, 1.9 g of diepoxy polyethylene glycol (Mn=20000) and 0.2 g of four-arm epoxy polyethylene glycol (Mn=20000) were added. After complete dissolution, 0.001 g of lithium hydroxide was added and the catalytic reaction was carried out for 2 h to form a supramolecular polymer network mixed solution for use.
[0037] 1g acrylamide, 1g sodium acrylate and 0.01g N,N-methylenebisacrylamide were dissolved in 6mL deionized water, and 0.03g supramolecular polymer network mixture was added. Under nitrogen protection, 5μL of 0.1g / mL copper nitrate solution was added. After mixing evenly, 0.005g initiator ammonium persulfate and 0.002g promoter tetramethylethylenediamine were added. The mixture was transferred into a polyfluoroethylene mold and allowed to stand for 30min to obtain a supramolecular hydrogel with high stretchability.
[0038] 1. Tensile test The highly stretchable supramolecular hydrogel obtained in this example was subjected to a stretching test. At room temperature, a hydrogel sample with a length of 4 cm, a width of 1 cm, and a thickness of 0.3 cm was placed in the fixture of a universal material testing machine, and the stretching rate was set to 10 mm / min. The supramolecular hydrogel was tested to be able to be stretched more than 10 times. Figure 1 shown.
[0039] 2. Tensile force and strain Experimental process: The copper nitrate solution in Example 1 was replaced with zinc nitrate solution, nickel nitrate solution, cobalt nitrate solution and ferrous nitrate solution with a concentration of 0.1 g / mL, respectively, and other conditions were kept unchanged. The prepared hydrogel was subjected to a tensile test in a universal material testing machine under the same conditions. The results are shown in FIG. Figure 2 shown. The amount of the supramolecular polymer network mixed solution added in Example 1 was adjusted from 0.03g (1.5wt%, Example 1) to 0g (no addition), 0.004g (0.2wt%), 0.01g (0.5wt%), 0.02g (1wt%), and 0.06g (2 wt%), respectively, while keeping other conditions unchanged. The prepared hydrogel was subjected to a tensile test in a universal material testing machine under the same conditions. The results are shown in FIG. Figure 3 shown.
[0040] from Figure 2 and Figure 3 It can be seen that the tensile stress of the hydrogel prepared by adding different metal cation solutions and different mass fractions of supramolecular polymer network mixtures will change. Different metal cations can increase the tensile length of the original polypropylene-based hydrogel, among which copper ions have the best effect. The addition of different mass fractions of supramolecular polymer network mixtures will significantly increase the maximum elongation of the original polypropylene-based hydrogel. As the mass fraction of the added solution increases, the strain of the hydrogel also increases. However, the addition of excessive supramolecular polymer network mixtures will increase its brittleness and reduce the tensile effect.
[0041] 3. Cyclic tension and compression test The hydrogel prepared in Example 1 was subjected to a cyclic tensile test, with a tensile rate of 10 mm / min and a tensile strain set to 1000% of the raw material. Figure 4 The hydrogel prepared in Example 1 was subjected to a cyclic compression test, with the compression rate set to 5 mm / min and the maximum compression strain set to 80% of the raw material. Figure 5 As shown in the figure, it can be seen that after 5 cycles of compression, the stress has basically not changed, which shows that the addition of the supramolecular polymer network does play a dissipative role and increases the mechanical properties of the hydrogel.
[0042] 4. Stability The hydrogel prepared in Example 1 was placed for 2 days and then subjected to a tensile test, and its mechanical properties were almost not reduced, indicating that the hydrogel prepared in the present invention has good stability.
[0043] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-stretchability pillar aromatic polypropylene hydrogel, characterized in that: Pillar aromatic compounds, 4,4'-bipyridine compounds and polyethylene glycol are mixed to obtain supramolecular polymers, which are then added to water mixed with acrylamide, sodium acrylate and N,N-methylenebisacrylamide, and prepared by adding metal ions, initiators and promoters.
2. The method for preparing the high-stretchability pillar aromatic polypropylene hydrogel according to claim 1, characterized in that: Here are the steps: (1) Add pillar aromatic compound a and 4,4-bipyridine compound b into water and mix at room temperature for 1.5-3 hours to obtain a pseudorotaxane, wherein The structural formula of pillar aromatic compound a is: , The structural formula of 4,4-bipyridine compound b is: ; (2) adding diepoxy polyethylene glycol and four-arm epoxy polyethylene glycol to the pseudorotaxane obtained in step (1) to obtain a mixed solution H, and adding lithium hydroxide to carry out a catalytic reaction after the mixed solution H is completely dissolved to obtain a supramolecular polymer; (3) acrylamide, sodium acrylate and N,N-methylenebisacrylamide are dissolved in water, and the supramolecular polymer obtained in step (2) is added. Under the protection of an inert gas, a metal ion solution is added, and the mixture is mixed evenly to obtain a mixed solution P. Then, an initiator and a promoter are added, and the mixture is allowed to react to obtain a highly stretchable supramolecular hydrogel.
3. The method for preparing the high-stretchability pillar aromatic polypropylene hydrogel according to claim 2, characterized in that: In step (1), the molar ratio of the pillar aromatic compound a to the 4,4-bipyridine compound b is 1:
1.
4. The method for preparing the high-stretchability pillar aromatic polypropylene hydrogel according to claim 2, characterized in that: The mass fraction of the pseudorotaxane in the mixed solution H of step (2) is 9-11%, the molecular weights of the diepoxy polyethylene glycol and the four-arm epoxy polyethylene glycol are 1000-20000; and the molar ratio of the diepoxy polyethylene glycol to the four-arm epoxy polyethylene glycol is (35-40):
1.
5. The method for preparing the high-stretchability pillar aromatic polypropylene hydrogel according to claim 2, characterized in that: In step (3), the mass ratio of supramolecular polymer: acrylamide: sodium acrylate: N,N-methylenebisacrylamide is (0.2-2): (90-110): (90-110): (0.8-1.2), the inert gas is nitrogen, the metal ion solution is any one of copper nitrate solution, zinc nitrate solution, ferrous nitrate solution, cobalt nitrate solution, and nickel nitrate solution, and the concentration of metal ions in the mixed solution P is 0.05-0.2 g / mL.
6. The method for preparing the high-stretchability pillar aromatic polypropylene hydrogel according to claim 2, characterized in that: In step (3), the initiator is ammonium persulfate or potassium persulfate, and the accelerator is tetramethylethylenediamine.
7. A highly stretchable pillar aromatic polypropylene hydrogel prepared by the method of any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of acrylamide-polyvinyl alcohol-acrylic acid-calcium chloride three-network compound hydrogel
CN107603106A
Preparation method of high-stretchability polyaniline-based flexible electrically conductive hydrogel
CN110157013A
Polyrotaxane quasi-slip ring hydrogel as well as preparation method and application thereof
CN115124662A
Cellulose / acrylamide super-tensile and adhesive hydrogel and preparation method thereof
CN115746208A
Functionalized pillararene polyrotaxane as well as preparation method and application thereof
CN117004037A